Efektivitas Pemberian Jus Alpukat (Persea Americana Mill) Terhadap Penurunan Dismenore Primer - Tri Marini SN; Nilda Yulita Siregar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Dysmenorrhea is menstrual pain that occurs in the lower abdomen and spreads to the back, waist, pelvis, upper thighs, and calves. The cause of dysmenorrhea is an increase in prostaglandin levels so that the contractility of the uterine muscle is ischemic as a result of the vasoconstrictive effect produced by prostaglandins. According to data from the World Health Organization (WHO) the prevalence of dysmenorrhea in adolescents is 90% consisting of 75% -80% primary dysmenorrhea and 10% - 15% experiencing secondary dysmenorrhea, while data from the Association of Southeast Asian Nations (ASEAN) prevalence of primary dysmenorrhea in Malaysia (69.4%), Thailand (84.2%), and Indonesia (65%). The prevalence of dysmenorrhea in Indonesia in 2018 was 64.25% consisting of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. This study aims to determine the effectiveness of administering avocado juice (Persea americana Mill) on reducing the rate of primary dysmenorrhea in first-level students of applied undergraduate study programs at the Indonesian Ministry of Health Polytechnic in Medan in 2023.The type of research used was Quasi Experiment with One Group Pretest and Posttest design. The sample in the study amounted to 30 people. The results of the research on the experimental group obtained a decrease in menstrual pain scale with an average of 2.66. The results of the analysis using the Wilcoxon test with a 95% level of confidence show a Sig (2-tailed) value of <0.05, which means that there is an effect of giving avocado juice on a decrease in primary dysmenorrhea in first level female students of the Bachelor of Applied Midwifery Study Program, Poltekkes Kemenkes Medan in 2023. It is expected that Poltekkes Kemenkes Medan to be able to utilize avocado fruit which is processed into juice in reducing menstrual pain in female students and for future researchers to be able to use my thesis as a reference.